Adding Insult to Injury: Sex, Sexual Orientation, and Juror Decision-Making in a Case of Intimate Partner Violence. Issue 10 (24th August 2018) - Stanziani, Marissa; Cox, Jennifer; Coffey, C. Adam
ABSTRACT: Societal definitions of intimate partner violence (IPV) are highly gendered and heteronormative, resulting in dissonance regarding cases of same-sex IPV. This study explored perceptions of IPV when the context of the case is inconsistent with societal norms regarding sex and sexuality. Mock jurors read a vignette describing a case of alleged IPV in which the sex and sexual orientation of the defendant were manipulated. Participants ( N  = 415) rendered a verdict and provided ratings of the defendant, victim, and case. Results suggest participants were more confident in a guilty verdict when the defendant was male, compared to female. Further, male defendants were perceived as more morally responsible, but only when the victim was female. Perceptions regarding the crime suggest violence perpetrated by a man against a woman is viewed more adversely than any other condition. Data are discussed in terms of implications for legal decision-makers and public policy.